2011
DOI: 10.1002/lsm.21023
|View full text |Cite
|
Sign up to set email alerts
|

Variation of fluorescence in tissue with temperature

Abstract: Cooling a tissue increased fluorescence intensity of skin in vivo, in all experiments. In vitro results were consistent with in vivo measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…The fluorescence decrease observed in Figure 3 is similar to the trends reported by Menter 13, Buttemere et al 24, and Zaman et al 25. Menter 13 tested the reversibility of the temperature‐induced fluorescence loss in extracted collagen and found that the recovery exhibited hysteresis.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The fluorescence decrease observed in Figure 3 is similar to the trends reported by Menter 13, Buttemere et al 24, and Zaman et al 25. Menter 13 tested the reversibility of the temperature‐induced fluorescence loss in extracted collagen and found that the recovery exhibited hysteresis.…”
Section: Discussionsupporting
confidence: 85%
“…Lin et al 15 observed in liver tissue that the fluorescence intensity changed as the tissue temperature was increased during radio‐frequency ablation. Zaman et al 19 conducted a study to explore the effect of temperature on tissue fluorescence of porcine sclera in vitro , and hamster skin in vivo and showed that the fluorescence peak height decreased with increased temperature. This attempt to explore the temperature dependence of fluorescence did not examine the thermally induced changes in optical properties and how these optical property changes influence the fluorescence yield.…”
Section: Introductionmentioning
confidence: 99%
“…This is linked to a decrease in the fluorescence signal intensity on a pixel‐by‐pixel basis. Previously published results in enucleated pig eyes and hamster skin confirmed this observation (Zaman et al ., ). A different behaviour was observed at the cell membrane, where the temperature consistently appears to be lower, in accordance with the results shown in Figure .…”
Section: Resultsmentioning
confidence: 97%
“…For example, in lung tissue, steep variations in the experimental data are likely due to ex vivo tissue manipulations, such as dilution errors, large temperature variations, 18 bacterial contamination of some samples or intersample variations due to differential blood oxygenation or blood retention. The model autofluorescence predictions were previously validated under fully controlled experimental conditions (using liquid phantoms of known optical properties).…”
Section: Autofluorescence Versus Tissue Dilutionmentioning
confidence: 99%